International Tourism Economic Cooperation Model under the Background of the Belt and Road Initiative - Wang, Yiming (Journal of Global Economy, Business and Finance, 2025)
This study empirically investigates the interactive dynamics between the “flow of people” (international tourism) and the “flow of goods” (import-export trade) in China-Turkey relations from 2014 to 2024, utilizing existing statistical data analysis. The findings reveal that the relationship is context-dependent. While tourism flows and trade volumes exhibit short-term co-movement when confronted with major external shocks, they frequently diverge under normal circumstances due to distinct driving mechanisms. Furthermore, a time-lag effect is identified, suggesting that the facilitative impact of tourism on trade materializes over a longer term rather than instantaneously. Consequently, this paper proposes that China and Turkey should enhance policy coordination, deepen cultural and tourism integration, and optimize their trade structure to improve the synergy and resilience of bilateral economic and personnel exchanges.